2016
DOI: 10.1098/rspb.2016.1453
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of bacterial recombinase A ( recA ) in eukaryotes explained by addition of genomic data of key microbial lineages

Abstract: Recombinase enzymes promote DNA repair by homologous recombination. The genes that encode them are ancestral to life, occurring in all known dominions: viruses, Eubacteria, Archaea and Eukaryota. Bacterial recombinases are also present in viruses and eukaryotic groups (supergroups), presumably via ancestral events of lateral gene transfer. The eukaryotic recA genes have two distinct origins (mitochondrial and plastidial), whose acquisition by eukaryotes was possible via primary (bacteria-eukaryote) and/or seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
9
0
2
Order By: Relevance
“…We also identified at least eight proteins likely involved in mitochondrial DNA recombination and/or repair, notably including an ortholog of the previously identified alphaproteobacteria-affiliated RecA proteins occurring in mitochondria of certain protists and plants (Additional file 3: Figure S1 (B)). The phylogenetic distribution and affinity of mitochondrial RecA has previously been studied by Hofstatter et al [84], who concluded that the protein has likely been secondarily lost in Discoba.…”
Section: Other Respiratory Proteinsmentioning
confidence: 99%
“…We also identified at least eight proteins likely involved in mitochondrial DNA recombination and/or repair, notably including an ortholog of the previously identified alphaproteobacteria-affiliated RecA proteins occurring in mitochondria of certain protists and plants (Additional file 3: Figure S1 (B)). The phylogenetic distribution and affinity of mitochondrial RecA has previously been studied by Hofstatter et al [84], who concluded that the protein has likely been secondarily lost in Discoba.…”
Section: Other Respiratory Proteinsmentioning
confidence: 99%
“…In secondary endosymbiosis, there exist clear and well‐known examples for such nested phylogenies that are furthermore independently corroborated by the presence of novel organelles (secondary plastids) in the recipient lineages. For example, the symbiotic origin of red secondary plastids generates trees in which plastid‐derived genes of diatoms branch nested within red algae, and the symbiotic origin of green secondary plastids generates trees in which plastid‐derived genes of chlorarachniophytes branch nested within chlorophytes . There are many such examples in the literature .…”
Section: Case Study: Eukaryote Anaerobes and Lgt In Endosymbiotic mentioning
confidence: 99%
“…This pattern is common between Arcella and Dictyostelium, and many eukaryotic repair machineries are actually derived from archaea and are conserved between eukaryotes and prokaryotes (Hofstatter et al. ; Makarova et al. ).…”
Section: Resultsmentioning
confidence: 98%